Application and feasibility of systemic lupus erythematosus reproductive health care quality indicators at a public urban rheumatology clinic. (February 2015) - Quinzanos, I; Davis, L; Keniston, A; Nash, A; Yazdany, J; Fransen, R; Hirsh, J M; Zell, J
Objectives: Quality indicators (QIs) are evidence-based processes of care designed to represent the current standard of care. Reproductive health QIs for the care of patients with systemic lupus erythematosus (SLE) have recently been developed, and examine areas such as pregnancy screening for autoantibodies, treatment of pregnancy-associated antiphospholipid syndrome, and contraceptive counseling. This study was designed to investigate our performance on these QIs and to explore potential gaps in care and demographic predictors of adherence to the QIs in a safety-net hospital. Methods: We performed a record review of patients with a diagnosis of SLE at Denver Health Medical Center (DH) through an electronic query of existing medical records and via chart review. Data were limited to female patients between the ages of 18 and 50 who were seen between July 2006 and August 2011. Results: A total of 137 female patients between the ages of 18 and 50 were identified by ICD-9 code and confirmed by chart review to have SLE. Of these, 122 patients met the updated 1997 American College of Rheumatology SLE criteria and had intact reproductive systems. Only 15 pregnancies were documented during this five-year period, and adherence to autoantibody screening was 100 percent. We did not have any patients who were pregnant and met criteria for pregnancy-associated antiphospholipid syndrome. Sixty-five patients (53%) received potentially teratogenic medications, and 30 (46%) had documented discussions about these medications' potential risk upon their initiation. Predictors of whether patients received appropriate counseling included younger age (OR 0.92, CI 0.87–0.98) and those who did not describe English as their primary language (OR 0.24, CI 0.07–0.87) in the multivariate analysis. Conclusions: We were able to detect an important gap in care regarding teratogenic medication education to SLE patients of childbearing potential in our public health academic clinic, as only one in two eligible patients had documented appropriate counseling at the initiation of a teratogenic medication.